Excretion of low molecular weight, folin-positive metabolites by the female receptor mycelium, in response to mating. - R. A. Prade; H. F. Terenzi (Fungal Genetics Reports, 1984)
Excretion of low molecular weight, folin-positive metabolites by the female receptor mycelium, in response to mating.